2021
DOI: 10.1055/s-0041-1730041
|View full text |Cite
|
Sign up to set email alerts
|

Association between Interleukin-1β Gene Polymorphism and Chronic Periodontitis

Abstract: Objectives Periodontitis is a pathological condition of the oral cavity, originating from multiple factors, including microbial, environmental and genetic factors. The vulnerability to several pathologies has been studied with the relationship to genetic polymorphisms, and one of the most prominent is the single nucleotide polymorphisms throughout the genome. The study aimed to find out the association of single nucleotide polymorphism (SNP) of interleukin-1β +3954 gene with chronic periodontitis (CP) in Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…IL-1β +3954 gene polymorphism is associated with periodontitis and is expected to be among the several causes of respective pathology. 23…”
Section: Apical Periodontitis and Osteoporosis Pathologymentioning
confidence: 99%
“…IL-1β +3954 gene polymorphism is associated with periodontitis and is expected to be among the several causes of respective pathology. 23…”
Section: Apical Periodontitis and Osteoporosis Pathologymentioning
confidence: 99%
“…Moreover, studies have found that genetic disparities among the population are associated with differences in the severity and development of periodontitis. [6][7][8] Maintaining oxygen homeostasis is an essential prerequisite for the viability of multicellular organisms. 9 Hypoxia is a physiological state characterized by a reduction in the availability of molecular oxygen (O2) or is linked to a disruption in the regulation of oxygen levels during intracellular redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have found that genetic disparities among the population are associated with differences in the severity and development of periodontitis. 6 7 8…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various studies have discovered that genotypic polymorphisms are connected with phenotypic variety, such as periodontitis severity and onset. [9][10][11][12][13] One such polymorphism is the NLRP3, there are a few studies that have looked at the NLRP3 polymorphism as it relates to periodontitis. 14 Hence, the purpose of this study was to explore the association of polymorphisms in the NLRP3 gene with periodontitis in the Arabs populations of Iraq.…”
Section: Introductionmentioning
confidence: 99%